Islamic Banking Performance: Important Insights and Strategies - Mubarok, Faizul; Sabrina, Kayla Nur; Muna, Putri Naelul; Maulida, Zahra (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2024)
Banks are financial institutions are created for the purpose of aggregating and disbursing funds among the members of the community. Such operation aims at financial equality, and serves the purpose of creating a platform for stimulating economic growth and overall national stability, which is directed toward the community well being. The main objective of this research is to analyze the impacts of Return on Equity and Debt to Equity Ratio, Gross Domestic Product, and Exchange Rate on Return on Equity in the Islamic banking institutions. The research adopts Islamic banking institutions in Indonesia and consists of five Islamic banks as a purposeful sampling method. To conduct the statistical analysis the Random Effect Model is employed. The research analyzes the impact of these selected financial variables: Return on Equity, Debt to Equity Ratio, Gross Domestic Product, and Exchange Rate Impact on Return on Equity. The researcher has concluded that Return on Equity, Debt to Equity Ratio, and Gross Domestic Product have significant impact on the Islamic banks Return on Equity. Exchange Rate on the other hand has no significant impact on the Islamic banks Return on Equity. To sum up this research, this study provides a basis for an understanding of the staticial relationship between ROE, DER, and GDP and ER on Return on Equity in Islamic banks. The understanding of such mechanism is a key premise for creating impact policies, which strategically improve then Islamic banks capabilities to grow and contribute to the country’s wellbeing.